Selective and eco-friendly procedures for the synthesis of benzimidazole derivatives. The role of the Er(OTf)3 catalyst in the reaction selectivity - Herrera Cano, Natividad; Uranga, Jorge G.; Nardi, Mónica; Procopio, Antonio; Wunderlin, Daniel A.; Santiago, Ana N. (Beilstein Journal of Organic Chemistry, 2016)
An improved and greener protocol for the synthesis of benzimidazole derivatives, starting from o-phenylenediamine, with different aldehydes is reported. Double-condensation products were selectively obtained when Er(OTf)3 was used as the catalyst in the presence of electron-rich aldehydes. Conversely, the formation of mono-condensation products was the preferred path in absence of this catalyst. One of the major advantages of these reactions was the formation of a single product, avoiding extensive isolation and purification of products, which is frequently associated with these reactions.Theoretical calculations helped to understand the different reactivity established for these reactions. Thus, we found that the charge density on the oxygen of the carbonyl group has a significant impact on the reaction pathway. For instance, electron-rich aldehydes better coordinate to the catalyst, which favours the addition of the amine group to the carbonyl group, therefore facilitating the formation of double-condensation products.Reactions with aliphatic or aromatic aldehydes were possible, without using organic solvents and in a one-pot procedure with short reaction time (2–5 min), affording single products in excellent yields (75–99%). This convenient and eco-friendly methodology offers numerous benefits with respect to other protocols reported for similar compounds.
Keywords: catalysis; charge density; condensation; erbium(III) trifluoromethanesulfonate; green procedure; heterocycle

Heterocyclic Chemistry in Drug Discovery - Li, J. J. (John Wiley &Sons, 2013)

(untitled) - Klingensmith, M. J.; Norman, A. G. (Science, 1960)

(untitled) - Denny, W. A.; Rewcastle, G. W.; Baguley, B. C. (J. Med. Chem., 1990)

(untitled) - Tebbe, M. J.; Spitzer, W. A.; Victor, F.; Miller, S. C.; Lee, C. C.; Sattelberg, T. R., Sr; McKinney, E.; Tang, J. C. (J. Med. Chem., 1997)

(untitled) - Porcari, A. R.; Devivar, R. V.; Kucera, L. S.; Drach, J. C.; Townsend, L. B. (J. Med. Chem., 1998)

(untitled) - White, A. W.; Almassy, R.; Calvert, A. H.; Curtin, N. J.; Griffin, R. J.; Hostomsky, Z.; Maegley, K.; Newell, D. R.; Srinivasan, S.; Golding, B. T. (J. Med. Chem., 2000)

(untitled) - Boiani, M.; Gonzalez, M. (Mini-Rev. Med. Chem., 2005)

(untitled) - Azam, M. A.; Suresh, B. (Sci. Pharm., 2012)

(untitled) - Herrera Cano, N.; Ballari, M. S.; López, A. G.; Santiago, A. N. (J. Agric. Food Chem., 2015)

(untitled) - Davey, D.; Erhadt, P. W.; Lumma, W. C., Jr; Wiggins, J.; Sullivan, M.; Pang, D.; Cantor, E. (J. Med. Chem., 1987)

(untitled) - Tomczuk, B. E.; Taylor, C. R., Jr; Moses, L. M.; Sutherland, D. B.; Lo, Y. S.; Johnson, D. N.; Kinnier, W. B.; Kilpatrick, B. F. (J. Med. Chem., 1991)

(untitled) - Spasov, A. A.; Yozhitsa, I. N.; Bugaeva, L. I.; Anisimova, V. A. (Pharm. Chem. J., 1999)

(untitled) - Mariappan, G.; Hazarika, R.; Alam, F.; Karki, R.; Patangia, U.; Nath, S. (Arabian J. Chem., 2015)

(untitled) - Salahuddin; Shaharyar, M.; Mazumder, A.; Ahsan, M. J. (Arabian J. Chem., 2014)

(untitled) - Ghosh, P.; Mandal, A. (Tetrahedron Lett., 2012)

(untitled) - Kumar, D.; Kommi, D. N.; Chebolu, R.; Garg, S. K.; Kumar, R.; Chakraborti, A. K. (RSC Adv., 2013)

(untitled) - Girish, Y. R.; Sharath Kumar, K. S.; Thimmaiah, K. N.; Rangappa, K. S.; Shashikanth, S. (RSC Adv., 2015)

(untitled) - Chebolu, R.; Kommi, D. N.; Kumar, D.; Bollineni, N.; Chakraborti, A. K. (J. Org. Chem., 2012)

(untitled) - Senthilkumar, S.; Kumarraja, M. (Tetrahedron Lett., 2014)

(untitled) - Kumar, A.; Kapoor, K. K. (J. Chem. Pharm. Res., 2011)

(untitled) - Fan, L.; Kong, L.; Chen, W. (Heterocycles, 2015)

(untitled) - Zhang, H.; Zhou, Z.; Yao, Z.; Xu, F.; Shen, Q. (Tetrahedron Lett., 2009)

(untitled) - Procopio, A.; Costanzo, P.; Curini, M.; Nardi, M.; Oliverio, M.; Sindona, G. (ACS Sustainable Chem. Eng., 2013)

(untitled) - Nardi, M.; Herrera Cano, N.; Costanzo, P.; Oliverio, M.; Sindona, G.; Procopio, A. (RSC Adv., 2015)

(untitled) - Nardi, M.; Sindona, G.; Costanzo, P.; Oliverio, M.; Procopio, A. (Tetrahedron, 2015)

(untitled) - Procopio, A.; Alcaro, S.; Nardi, M.; Oliverio, M.; Ortuso, F.; Sacchetta, P.; Pieragostino, D.; Sindona, G. (J. Agric. Food Chem., 2009)

(untitled) - Procopio, A.; Celia, C.; Nardi, M.; Oliverio, M.; Paolino, D.; Sindona, G. (J. Nat. Prod., 2011)

(untitled) - Nardi, M.; Bonacci, S.; De Luca, G.; Maiuolo, J.; Oliverio, M.; Sindona, G.; Procopio, A. (Food Chem., 2014)

(untitled) - Nardi, M.; Cozza, A.; Maiuolo, L.; Oliverio, M.; Procopio, A. (Tetrahedron Lett., 2011)

(untitled) - Nardi, M.; Cozza, A.; De Nino, A.; Oliverio, M.; Procopio, A. (Synthesis, 2012)

(untitled) - Bahrami, K.; Khodaei, M. M.; Nejati, K. (Green Chem., 2010)

(untitled) - Zhang, L.-J.; Xia, J.; Zhou, Y.-Q.; Wang, H.; Wang, S.-W. (Synth. Commun., 2012)

(untitled) - Jacob, R. G.; Dutra, L. G.; Radatz, C. S.; Mendes, S. R.; Perin, G.; Lenardão, E. J. (Tetrahedron Lett., 2009)

(untitled) - Patil, P. P.; Deshmukh, M. B.; Mulik, A. G.; Chandam, D. R.; Patil, D. R.; Jagdale, S. D.; Anbhule, P. V.; Salunkhe, D. K.; Sankpal, S. A. (Pharma Chem., 2011)

(untitled) - Shitole, N. V.; Niralwad, K.; Shingate, B. B.; Shingare, M. S. (Arabian J. Chem., 2012)

(untitled) - Wan, J.-P.; Gan, S.-F.; Wu, J.-M.; Pan, Y. (Green Chem., 2009)

(untitled) - Nile, S. H.; Kumar, B.; Park, S. W. (Arabian J. Chem., 2015)

(untitled) - Chen, G.-F.; Shen, H.-D.; Jia, H.-M.; Zhang, L.-Y.; Kang, H.-Y.; Qi, Q.-Q.; Chen, B.-H.; Cao, J.-L.; Li, J.-T. (Aust. J. Chem., 2013)

(untitled) - Lin, S.; Yang, L. (Tetrahedron Lett., 2005)

(untitled) - Du, L.-H.; Wang, Y.-G. (Synthesis, 2007)

(untitled) - Chen, C.; Chen, C.; Li, B.; Tao, J.; Peng, J. (Molecules, 2012)

(untitled) - Park, S.; Jung, J.; Cho, E. J. (Eur. J. Org. Chem., 2014)

Gaussian 09, Revision B.01 (Gaussian, Inc., 2010)